Individual and combined effects of Bacillus thuringiensis var. israelensis, temephos and Leptolegnia chapmanii on the larval mortality of Aedes aegypti - Pelizza, Sebastián Alberto (2010)
Larvicidal effects of interaction between Bacillus thuringiensis var. israelensis (Bti), temephos and Leptolegnia chapmanii zoospores on larvae of Aedes aegypti were determined under laboratory and seminatural conditions. In laboratory bioassays, two concentrations of Bti (0.012, 0.027 ppm), two of temephos (0.00035, 0.001 ppm), and a single concentration of L. chapmanii zoospores (6.1 × 10⁴ zoospores ml⁻¹) were evaluated. Trials under field-like conditions were performed in a single container and then placed either in the shade or in direct exposure to sunlight. We evaluated concentrations of Bti and temephos at 3-fold those normally used in laboratory tests: 0.09 and 0.003 ppm, respectively, plus 1.8 × 10⁵ zoospores ml⁻¹ of L. chapmanii. The combined effect of sublethal concentrations of Bti, temephos, and L. chapmanii zoospores thus indicated that this fungus is not inhibited by the larvicides and also demonstrated the synergistic effect of the action of L. chapmanii when used together with Bti and temephos.